Biomineralization and synthesis of biogenic magnetic nanoparticles and magnetosensitive inclusions in microorganisms and fungi - Gorobets, O.Yu.; Gorobets, S.V.; Sorokina, L.V. (Functional Materials, 2014)
In this study the identification of proteins which are homologous to Mam proteins of magnetotactic bacteria (MTB) Magnetospirillum gryphiswaldense MSR-1 was performed. Using the bioinformatics methods it was revealed the role of these proteins in synthesis of extracellular and intracellular, crystalline and amorphous magnetosensitive structures (MsS) in magnetotactic microorganisms (MO) of different taxonomic groups, including fungi. The analysis of the results of alignments of Mam-proteins of MTB and the proteins of non-magnetotactic MO synthesizing MsS allowed to classify the investigated MO to 4 groups in which MO differ in their properties and localization of synthesized MsS (extracellular amorphous, extracellular crystalline, intracellular amorphous and intracellular crystalline MsS) that correlates with the presence of the certain Mam homologues in proteome. The obtained results could be useful for identification of the MO potentially producing MsS with the certain properties for different application in medicine, biometallurgy, nanoelectronics.